Effects of leadership styles and organizational cultures on organizational performance of Amman Stock Exchange (ASE) companies: a focus on the moderating effects of internal control system. - Ershaid, Diala Jehad (2021)
This study observes the effect of leadership styles and organizational cultures on the organizational performance of Jordanian companies listed on Amman Stock Exchange (ASE). Specifically, it examines the internal control system components as a moderating effect within this relationship. The theories used to underpin the analysis are contingency, transformational-transactional, and resource-based view theories. The study utilizes a survey method in which 233 questionnaires were distributed into three different sectors based on ASE. However, only 208 questionnaires were returned of which only 190 questionnaires were valid for a test analysis using PLS-SEM. The results showed a positive and significant relationship between leadership style and organizational performance only in transformational, but not in transactional leadership. The study also found items of organizational culture; bureaucratic, and innovative to have a significant relationship with performance, however supportive item did not show any affect. At the same time, internal control systems emerged as a moderator in the relationship between leadership style, organizational culture, and organizational performance. Internal control system of risk assessment and monitoring acted to moderate the relationship between leadership style and organizational performance. Nevertheless, monitoring was also found to moderate the relationship between organizational culture and organizational performance. Besides, the results indicated that control environment and, information and communication system moderate the relationship between organizational culture and organizational performance. As a conclusion, this study indicates that by understanding highly related influential factors and managing them would effectively improve organizational performance in ASE. Furthermore, the study highlights the importance of internal control system applied in ASE companies, and motivates the possibility of extending the research in other parts of developing countries worldwide.